TELAAH FILOSOFIS INTEGRASI AKAL DAN WAHYU: RELEVANSINYA TERHADAP PENDIDIKAN ISLAM YANG HOLISTIK - Muhammad Fatih Arroichan; Fikri Al-Huda Febrian; Muhammad In’am Esha; Imron Rossidy (STKIP Subang, 2026)
This study aims to analyze the integration of reason (ʿaql) and revelation (waḥy) from an Islamic perspective and to examine its relevance to the development of holistic Islamic education. The study is motivated by the growing dichotomy between religious and secular sciences, which has led to the fragmentation of knowledge, moral crises, and an imbalance between intellectual and spiritual development in contemporary education. This research employs a library research method with a content analysis approach. Primary sources include the works of Al-Ghazali, Ibn Rushd, Syed Muhammad Naquib al-Attas, Ismail Raji al-Faruqi, and Fazlur Rahman, while secondary sources consist of relevant scholarly books and journal articles. The findings reveal that reason and revelation are complementary sources of knowledge within Islamic epistemology. Reason functions as an instrument for understanding reality and developing knowledge through rational inquiry, whereas revelation provides moral guidance, values, and ultimate purpose for the application of knowledge. Their integration produces a holistic epistemological paradigm capable of overcoming the dichotomy of knowledge and situating scientific inquiry within a tawḥidic framework. Furthermore, this paradigm is highly relevant to the development of Islamic education, particularly in shaping educational goals, curriculum design, learning processes, the role of educators, and evaluation systems that integrate intellectual, spiritual, moral, and social dimensions. Therefore, the integration of reason and revelation offers a conceptual foundation for developing a more balanced, humanistic, and context-responsive model of holistic Islamic education.